The Role of Wordwall Gamification Mechanics in Developing Higher Level Thinking Skills (HOTS) of Elementary Science Students: A Systematic Review - Rohmani; Supriyono; Bunga Adelia (urn:multiple://2988-7828multiple.v3i105)
Modern education demands the development of Higher-Order Thinking Skills (HOTS), particularly in elementary school science learning. Gamification, through platforms like Wordwall, has emerged as a promising strategy to enhance motivation and stimulate high-level cognitive processes. However, existing research has not specifically analyzed which gamification mechanics contribute to HOTS development. This study aims to identify, analyze, and synthesize empirical evidence on the specific role of Wordwall's gamification mechanics in developing the HOTS of elementary science students through a Systematic Literature Review (SLR) using the PRISMA framework. A literature search was conducted on the Google Scholar database for articles published between 2020 and 2024. From an initial 686 articles, 6 met the inclusion criteria and were thematically analyzed. The analysis reveals that key mechanics such as (1) instant feedback and challenges promote the process of analysis; (2) interactivity and visualization facilitate interpretation and evaluation; and (3) elements of competition and time constraints are effective for measuring knowledge application within project/problem-based learning models. It is concluded that Wordwall is not merely a motivational tool but a strategic pedagogical instrument that, when designed appropriately, can effectively train various aspects of students' HOTS. While this review identifies key correlations, future experimental research is recommended to establish a direct causal relationship between these specific mechanics and the development of distinct HOTS components.